Abstract ID: 108 Study on conformal proton therapy using multileaf collimated beams without tumour-specific range compensators via flat dose-layer stacking. (October 2017) - Shao, Wencheng; Tang, Xiaobin; Geng, Changran; Shu, Diyun; Gong, Chunhui; Ai, Yao; Zhang, Xudong
Abstract : Purpose: In traditional conformal proton therapy (CPT), proximal dose conformity of tumours is sacrificed for achieving distal dose conformity due to tumour-specific range compensators. This study investigated whether CPT can be realized without tumour-specific range compensators using multileaf-collimated proton beams, and whether range-compensator-free CPT (RCF-CPT) can improve the proximal dose conformity without sacrificing distal conformity. Methods: First, geometric configurations of a virtual multileaf-collimator (MLC) and three tumour cases (brain, liver, and prostate) were adopted during Geant4 geometry setup. Second, conformal proton radiation fields were generated for tumour CT slices based on the predesigned MLC using Geant4. Third, flat dose-layers corresponding to these tumour slices were produced using dose patching method in which MLC-collimated subbeams can be utilized to modulate the dose uniformity of these flat dose-layers. Forth, these flat dose-layers were stacked and integrated throughout the tumours for obtaining sufficient tumour dose coverages. Furthermore, dosimetric comparisons between the RCF-CPT and traditional CPT were performed to detail the dosimetric advantages of RCF-CPT. Results: For the three tumour cases, the tumours can be sufficiently covered by 95% relative doses through RCF-CPT, and the maximum tumour doses were smaller than 110% relative doses. Approximately, the proximal doses of RCF-CPT were controlled to 60% relative doses, and 95% dose lines fit with the tumour profiles at proximal tumour regions. Conclusions: Compared with traditional CPT, RCF-CPT can highly enhance the proximal dose conformity of tumours without sacrificing distal conformity. Moreover, the workflows of CPT can be largely simplified based on the range-compensator-free characteristic of RCF-CPT.